(untitled) (Fiep Bulletin - online, 2015)
This research, of bibliographical, objective nature to present, from the produced studies, pedagogical proposals where the Eastern Martial Arts, from wushu (kung fu), contribute for the pertaining to school Physical Education in a context to transdisciplinar. The question that moved the study mentions the possibilities to it for the use, in special, of the Chinese Martial Arts for perceiving a confluence to know that they characterize it. The happened hypothesis of the problematizadora question points that the suggested proposals propitiate the integral development of the learning, if to contextualizarmos the practical with the social reality and historical express in the cultural production human being. As result, it points to be viable the inclusion of kung fu, if this proposal to keep the holistic nature that it is proper, prioritizing the development of the espontaneidade, creativity, sensitivity and intuition. Taking as base the challenge to direct an action line that would be capable to unchain a process integrator and participativo in the pertaining to school physical education, we find some of them where reason and emotion tend if to complement, despite if it cannot consider a true integration, as it is the case of the conventional and tecnicistas systems. Of this form, such practical, propagated in the pertaining to school physical education, assist to modify the routine established for the convencionalismo used in the practical esportivas. In one second tier, it is possible to develop the espontaneidade, the intuition and the creativity endorsing itself in the moreniana conception, and, therefore, Inter and transdisciplinar using experiences that prove the possibility of if promoting an education for the human development. Thus, the possibilities of the martial arts to contribuirem for the practical transforming motor if contemplated, despite we could see indistinctly measured conventional that, for force of the traditionalism of the eastern culture, tend if to reveal in the practical ones of education. With the gotten results, we could show as, where, what, so that and for who kung fu can be employee, also, as ecopedagógico instrument.